Analysis of Emergency Health Care Workforce and Service Readiness for a Mass Casualty Event in the Republic of Ireland. (21st May 2018) - Veenema, Tener Goodwin; Boland, Fiona; Patton, Declan; O'Connor, Tom; Moore, Zena; Schneider-Firestone, Sarah
ABSTRACT: Objective: Ultimately, a country's capacity for a large-scale major emergency response will be directly related to the competence of its health care provider (HCP) workforce and communication between emergency responders and hospitals. The purpose of this study was to assess HCP preparedness and service readiness for a major emergency involving mass casualties (mass casualty event or MCE) in Ireland. Methods: A cross-sectional study using a 53-item survey was administered to a purposive sample of emergency responders and HCPs in the Republic of Ireland. Data collection was achieved using the Qualtrics ® Research Suite. Descriptive statistics and appropriate tests of comparison between professional disciplines were conducted using Stata 13. Results: A total of 385 respondents, registered nurses (43.4%), paramedics (37.9%), medical doctors (10.1%), and administrators/managers (8.6%), participated in the study. In general, a level of knowledge of MCEs and knowledge of clinical response activities and self-assessed clinical competence varied drastically across many aspects of the survey. Knowledge and confidence also varied across professional disciplines ( P <0.05) with nurses, in general, reporting the least knowledge and/or confidence. Conclusions: The results demonstrate that serious deficits exist in HCP knowledge, skills, and self-perceived abilities to participate in a large-scale MCE. Results also suggest a poor knowledge base of existing major emergency response plans. ( Disaster Med Public Health Preparedness . 2019;13:243–255)